(untitled) (American Journal of Economics and Business Innovation, 2024)
This article provides an in-depth analysis of the key role of global supply chain stability in the international trade economy and the core role of efficient risk management in this process. Driven by the wave of globalization, supply chains have become a key link connecting the economies of various countries. This article provides a comprehensive analysis of the current status of global supply chains and an in-depth exploration of the many factors affecting supply chain stability, including supplier reliability, logistics system efficiency, demand forecast accuracy, and inventory management effectiveness. It further delves into many aspects of supply chain risk management, including risk identification, assessment, mitigation and monitoring. Analyze and formulate contingency plans for emergencies as well as regular monitoring and evaluation strategies and measures to improve the effectiveness and value of risk management. Finally, this study emphasizes the importance of supply chain stability and efficient risk management in the global foreign trade economic system, and provides suggestions for future research directions and possible improvement strategies. This research has far-reaching significance for enhancing the transparency, resilience and sustainability of global supply chains, and is crucial to the stable development of the global economy.